An unobserved components model for Finland – Estimates of potential output and NAWRU - Mikko Sariola (Bank of Finland, 2019)
In this paper, we estimate a potential output model for Finland using an unobserved component model. The model builds on a production function approach, and features price and wage Phillips curves, Okun's law and several resource-utilization indicators. We show that incorporating resource-utilization indicators, i.e. capacity utilization and long-term unemployment, improves real-time reliability of the output gap and NAWRU estimates. Our real-time estimate of the output gap is robust even in an event of a sudden turning point in the economy such as the global financial crisis. It also outperforms the HP filter estimate. Results suggest that Finland's potential output growth slowed significantly in the aftermath of the financial crisis and that the output gap was negative for most of the subsequent decade. The slowdown in potential growth was due mainly to lackluster total factor productivity growth. The real-time results are broadly in line with the ex-post estimates of the IMF and the European Commission.
URN:NBN:fi:bof-201904041133
Keywords: C51; E23; E32; 330; Suomi; potentiaalinen tuotanto; mallit; tuotantokuilu